2013
DOI: 10.2174/1874210601307010088
|View full text |Cite
|
Sign up to set email alerts
|

CRP and IL-1B Gene Polymorphisms and CRP in Blood in Periodontal Disease

Abstract: Recent studies have suggested an association between periodontal disease (PD) and the systemic polygenic diseases such as cardiovascular disease (CVD). These are thought to be associated because of interrelated environmental, epigenetic, and genetic risk factors. The involved candidate genes include the IL-1B gene, encoding the pro-inflammatory cytokine IL-1β, and the CRP gene encoding the C-reactive protein (CRP), also a known marker of inflammation. However, as the details are not well known on the genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Eight papers classified as poor, 1 as good, and the remaining 43 papers were of moderate quality (Figure ). The lowest score reached by a paper was 3, while the best score was 13 . The items most frequently deemed inadequate involved the handling of confounders, especially oral hygiene habits, socioeconomic status, presence of specific periodontal pathogens, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers classified as poor, 1 as good, and the remaining 43 papers were of moderate quality (Figure ). The lowest score reached by a paper was 3, while the best score was 13 . The items most frequently deemed inadequate involved the handling of confounders, especially oral hygiene habits, socioeconomic status, presence of specific periodontal pathogens, and stress.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules are necessary to bind leucocytes in the endothelium layer at the early stage of atherosclerosis. 16 These bacteria will produce a leucotoxin that induces degranulation and lysis in human neutrophils, caspase-1 activation, and abundant secretion of cytokine from human macrophages, promoting a tissue destruction including loss of alveolar bone. 17 Therefore, theoretical based revealed that the level of CRP by the induction of bacterial leucotoxin are supposed largely expressed in severe periodontitis group.…”
Section: Methodsmentioning
confidence: 99%
“…To identify ENAM C2452T polymorphism, we performed DNA isolation as described by Auerkari et al [15][16][17] and genotyping procedures as described by Ouryouji et al [14]. Each 20-µL polymerase chain reaction (PCR) mixture contained 10 µL of ready-to-use master mix (Bioline, London, UK), 0.4 µL of forward (5'-AGG ATT TTT ATT ACA GTG AAT TTT ACC CAT GGG GCC-3') and reverse primers (3'-CCT TAA GGA CCC TGG TGT CCT ATG TTC-5'), and 20 µg of genomic DNA.…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%